2019
DOI: 10.1002/jor.24416
|View full text |Cite|
|
Sign up to set email alerts
|

Kinematic Evaluation of the GMK Sphere Implant During Gait Activities: A Dynamic Videofluoroscopy Study

Abstract: Joint stability is a primary concern in total knee joint replacement. The GMK Sphere prosthesis was specifically designed to provide medial compartment anterior–posterior (A–P) stability, while permitting rotational freedom of the joint through a flat lateral tibial surface. The objective of this study was to establish the changes in joint kinematics introduced by the GMK Sphere prosthesis during gait activities in comparison to conventional posterior‐stabilized (PS) fixed‐bearing and ultra‐congruent (UC) mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 42 publications
3
67
0
Order By: Relevance
“…Despite small but significant differences in the in vivo measured kinematics (Schütz et al, 2019a), we found that posterior-stabilized, medial-stabilized, and ultra-congruent TKA designs all resulted in similar collateral elongation patterns (regardless of minor differences between their peaks) throughout complete cycles of level walking, downhill walking, and stair descent. The measured kinematics indicate that the GMK sphere implants indeed provide medial constraint, with the medial femoral condyle exhibiting a range of anterior-posterior translation of only 3.7 mm compared to 10.6 mm for PS, and 5.9 mm for UC implants during level walking.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Despite small but significant differences in the in vivo measured kinematics (Schütz et al, 2019a), we found that posterior-stabilized, medial-stabilized, and ultra-congruent TKA designs all resulted in similar collateral elongation patterns (regardless of minor differences between their peaks) throughout complete cycles of level walking, downhill walking, and stair descent. The measured kinematics indicate that the GMK sphere implants indeed provide medial constraint, with the medial femoral condyle exhibiting a range of anterior-posterior translation of only 3.7 mm compared to 10.6 mm for PS, and 5.9 mm for UC implants during level walking.…”
Section: Discussionmentioning
confidence: 51%
“…For example, the GMK Sphere (Medacta International, Switzerland) implant possesses a congruent spherical geometry on the medial side to provide anterior-posterior stability, and a relatively flat lateral tibial plateau to enable free movement of the lateral condyle. These intended implant motion patterns have indeed been confirmed through reconstruction of the 3D joint kinematics throughout both lunge movements and complete cycles of daily activities using mobile fluoroscopy (Scott et al, 2016; Schütz et al, 2019a). However, it is still not well-understood how such medially stabilized component designs affect the strains in the passive restraints of the knee.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Fluoroscopic imaging and image processing now enable the relative kinematics of the tibial and femoral implant components to be measured during restricted movements [ 20 , 21 , 22 ]. By using the reconstructed 3D kinematics of the joint, tracking of the relative displacements of attachment footprints then allows the elongation patterns of ligaments to be assessed [ 18 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%